The Arabidopsis Elongator Subunit ELP3 and ELP4 Confer Resistance to Bacterial Speck in Tomato - Pereira, Juliana A.; Yu, Fahong; Zhang, Yanping; Jones, Jeffrey B.; Mou, Zhonglin (Frontiers in Plant Science, 2018)
Although production of tomato (Solanum lycopersicum) is threatened by a number of major diseases worldwide, it has been difficult to identify effective and durable management measures against these diseases. In this study, we attempted to improve tomato disease resistance by transgenic overexpression of genes encoding the Arabidopsis thaliana Elongator (AtELP) complex subunits AtELP3 and AtELP4. We show that overexpression of AtELP3 and AtELP4 significantly enhanced resistance to tomato bacterial speck caused by the Pseudomonas syringae pv. tomato strain J4 (Pst J4) without clear detrimental effects on plant growth and development. Interestingly, the transgenic plants exhibited resistance to Pst J4 only when inoculated through foliar sprays but not through infiltration into the leaf apoplast. Although this result suggested possible involvement of stomatal immunity, we found that Pst J4 inoculation did not induce stomatal closure and there were no differences in stomatal apertures and conductance between the transgenic and control plants. Further RNA sequencing and real-time quantitative PCR analyses revealed a group of defense-related genes to be induced to higher levels after infection in the AtELP4 transgenic tomato plants than in the control, suggesting that the enhanced disease resistance of the transgenic plants may be attributed to elevated induction of defense responses. Additionally, we show that the tomato genome contains single-copy genes encoding all six Elongator subunits (SlELPs), which share high identities with the AtELP proteins, and that SlELP3 and SlELP4 complemented the Arabidopsis Atelp3 and Atelp4 mutants, respectively, indicating that the function of tomato Elongator is probably conserved. Taken together, our results not only shed new light on the tomato Elongator complex, but also revealed potential candidate genes for engineering disease resistance in tomato.